Notebook [32, Fall 1993] - Leier, Mark (James Mark) (Labour/Le Travail, 1993)
Reports forthcoming conferences and new publications. The Reuther Archives of Labour and Urban Affairs at Wayne State University is to be added to the National Bibliographic System. The Steel Project at University College of Cape Breton has a wide variety of archival resources on steelmaking technology and workers. The files of the Detroit Red Squad have been deposited at the Detroit Public Library, but will remain closed until 2018.